Wildflower farming on the Agulhas Plain : fynbos management and conservation - Treurnicht, Martina (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScConsEcol (Conservation Ecology and Entomology))--University of Stellenbosch, 2010.